A study on the validation of the drinking and abstaining behaviors: questionnaire among portuguese university students - Mostardinha, António Ramalho (2019)
Alcohol consumption among university students could be influenced by personal and environmental factors, where perceptions of behaviors are approved/disapproved and typically complied could be related to alcohol consumption. Considering the need to provide valid tools assessing descriptive/injunctive norms of drinking, our research question was: “What are the psychometric properties of the Drinking and Abstaining Behaviors Questionnaire (DABQ)?” We aimed to translate, cultural adapt and analyze the reliability and the construct validity of the Descriptive and Injunctive Norms of the DABQ (DN and IN) using 3 reference groups (Typical college students, Acquaintances and Good friends, to Portuguese university students. A validation, cross-sectional study was performed. The sample comprised 338 students (51.8% male), with a mean age of 20.6 years (SD= 3.4) from University of Aveiro, Portugal. To examine the factor structure of the Portuguese version, a Confirmatory Factor Analysis (CFA) was performed. Additionally, the internal consistency and convergent validity were also evaluated. Concerning the factor structure, the two-factor original model presented a better relative fit considering the DN in the three reference groups. For the IN, a modified two-factor model, showed a better relative fit to data considering the friends and closest friends. A satisfactory internal consistency was also found (.765<DN α<.891 and .675<IN α<.869). Our findings suggested DABQ is a valid tool in higher education settings. However, its factor structure should be (re)examined using CFA procedures within community samples.